EFFICIENCY OF BETADINE VS CHLORHEXIDINE VS NORMAL SALINE IN EXTRACTION GROUP OF PATIENTS. - John Francis; Dr. Vinod Krishna Krishnaswamy; Dr. Gidean Arularasan (Journal of Population Therapeutics and Clinical Pharmacology, 2022)
INTRODUCTION: An accessible tooth in your mouth is extracted gently if it needs to be removed. A general dentist frequently performs straightforward extractions. Your dentist will paralyze the area around the tooth and the gums, then use dental forceps to remove the tooth after loosening it using an elevator. MATERIALS AND METHODS: This was a randomized, double blind parallel study on the efficacy of the CHX for the prevention of a total of 30 study participants forming the sample size of this study. RESULTS: The patients were between the ages of 20 and 50. The mean age difference between the controls (31.4 years) and patients (36.6 years) was not statistically significant. CONCLUSION: The present study proves that betadine is shown with good prognosis and low incidence rate of dry socket and infection compared with CHX and normal saline.